Factor's indicating the performance in men's artistic gymnastics based on extracted variables at the initial stage of training - Prakhar Rathore; Sudhira Chandel (H.S. Skovoroda Kharkiv National Pedagogical University, 2023)
Purpose To develop the regression equation with the help of step wise method in linear regression. Material and methods In this study, 150 boy's gymnasts from National Sports Academy in Allahabad (India) (age 6+4 years; height 102+46; body weight 22+8) had participated and they provided informed consent before the testing procedure. Over Grip Hang on Horizontal Bar, Bridge up test, Leg Raise Forward, Front Split, Shuttle Run on Floor Exercise, Beam Walk Test, and Flexed Arm Hang on Horizontal Bar were selected as the testing variables and after using the liner regression analysis Results The equation was formed which estimates that Beam walk test, Shuttle run on Floor Exercise, Over grip hang on Horizontal, and Flexed arm hang on Horizontal bar account for 41% of the variation in the relation of dependent variables (Gymnastics Performance). Conclusion A thorough study of the factors that foster gymnast growth is essential since it is crucial in gymnastics to identify potential early in a player's career [16, 17, 22], for that extracted factors and gymnastics performance were selected to form the regression equation. The four variables selected to create the regression equation which explains 41 % of the total variability which is quite good and valid for estimating the Gymnastics Performance. Conclusion A thorough study of the factors that foster gymnast growth is essential since it is crucial in gymnastics to identify potential early in a player's career [16, 17, 22], for that extracted factors and gymnastics performance were selected to form the regression equation. The four variables selected to create the regression equation which explains 41 % of the total variability which is quite good and valid for estimating the Gymnastics Performance.